ANALISIS PELAKSANAAN PROGRAM ASISTENSI MENGAJAR DAN KAMPUS MENGAJAR BAGI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Kulata, Maria Ima; Asriati, Nuraini; Okianna, Okianna (Universitas Tanjungpura, 2023)
This research aims to determine and analyze the implementation of the MBKM Teaching Assistants and Kampus Mengajar program for students of the Economic Education study program FKIP UNTAN. The research method used is a case study with a qualitative approach. The data sources in this research are divided into two, namely primary sources which come from data from interviews with undergraduate students in Economic Education and the Head of the Economic Education Study Program. As well as secondary sources that come from documentation of the results of learning tools created by students while participating in the program and other documents that support research. The results of the research show that the implementation of the Teaching Assistants and Kampus Mengajar programs provides benefits for Economics Education students in the form of recognition for 20 credits of courses in the Economics Education study program, getting student living resources which are received every month, and teaching experience. Apart from that, another benefit that students also experience is in the form of improving soft skills. Even though both programs provide the same benefits, the impact received and felt by Economic Education students is different from each program implementation. So students must be wise in choosing the right program to follow.